Measurement of anxiety among students Primary stage (Journal of the College of Basic Education, 2022)
The child’s personality is affected by the type of social upbringing that he receives in the family and society and the experiences he goes through. The first years are considered one of the most important stages of his life, because of their great impact on the formation of his personality and the acquisition of habits, values ​​and attitudes. ).Childhood is the most important stage in human life, not only in terms of health and education, but also in terms of psychological formation. (Mohammed, 2006, p. 3).